Two new species of idoteid isopods (Crustacea, Isopoda, Idoteidae) from Korea - Kim, Sung Hoon; Jung, Tae Won; Yoon, Seong Myeong (Zootaxa, 2020)
Two new species, Cleantiella ampliscutula sp. nov. and Pentias pluriarticulatus sp. nov., are reported from Korean waters with keys to all known species of the genera Cleantiella and Pentias. Cleantiella ampliscutula sp. nov. can be distinguished from its congeners by the following characteristics: the body is relatively small; pereonite 1 is expanded anterolaterally; coxal plates 2–7 are triangular; the pleon has three partial sutures; the pleotelson is widening posteriorly on the lateral margin; the flagellum of the antenna is single-articled; and the maxillipedal palps are four-articled. Pentias pluriarticulatus sp. nov. can be distinguishable from its congeners by the following characteristics: the lateral margins of the body are parallel; the anterior margin of the cephalon is slightly concave and has a small median notch; the coxal plates are invisible dorsally on pereonites 2–4, but visible on pereonites 5–7; the pleon has three partial sutures; the flagellum of the antenna is composed of nine articles; and the distal ends of the uropodal endopods are sinuous.